Experiencia áulica para desarrollo de competencias en la enseñanza de sistemas de representación - Bombassei, Elisa Beatriz (2018)
One of the fundamental competences for all professionals is to be able to express themselves and be able to make known in different ways the results of their work, a proposal for a solution to a problem, a need, etc., therefore, without modifying the curricula of the subject of Drawing for the career of Chemical Engineering, has incorporated a space where students can express research results on specific topics of their career referred to the application of graphic models as a means of expression. In the present work, the results obtained from this experience in this first year of implementation are shown.